Satin and their crossbred rabbit production - Bram Brahmantiyo; Y.C Raharjo; H Martojo; S.S Mansjoer (Jurnal Ilmu Ternak dan Veteriner, 2010)
Rabbit productivity in intensive management to be evaluated considering development in the rabbit farming were rapidly increased. Rex, Satin and their crossbred (Reza) rabbits have been developed in Research Institute for Animal Production and productivity information of each breed can be used as basis for policy or model of cultivation and breeding in the community. Research conducted by evaluating the productivity of growth, carcass and the carcass proportion of the three strains of rabbit. Rex and satin growth were no different, and Reza was higher at 12-14 weeks of age. Carcass production comes from cutting the rabbit at the age of six months, this trait is strongly influenced by the weight of rabbits, and Reza gives the lowest performance compared to Rex and Satin. Rex, Satin and Reza were medium type rabbits with dual-purpose product (fur and meat). These rabbits showed the child's growth is good enough, to adapt the environment temperature and high food and have adequate carcass production. Key Words: Rabbit, Rex, Satin, Reza, Growth, Carcass